2023
DOI: 10.1101/2023.08.17.553673
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cryo-EM of soft-landedβ-galactosidase: Gas-phase and native structures are remarkably similar

Tim K. Esser,
Jan Böhning,
Alpcan Önür
et al.

Abstract: Native mass spectrometry (native MS) is a powerful technique that provides information on stoichiometry, interactions, homogeneity and shape of protein complexes. However, the extent of deviation between protein structures in the mass spectrometer and in solution remains a matter of debate. Here, we uncover the gas-phase structure of β-galactosidase using single particle electron cryomicroscopy (cryo-EM) down to 2.6 A resolution, enabled by soft-landing of mass-selected protein complexes onto cold TEM grids an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 68 publications
0
9
0
Order By: Relevance
“…We believe the future work outlined above will provide a path for continued improvements that ultimately allow for the direct coupling of MS with cryo-EM. Finally, we note that while this manuscript was under peer review, a preprint describing a similar cryogenic ion landing apparatus has been released by Esser et al Collectively, these joint works provide strong evidence for the potential impact of this exciting new field.…”
Section: Discussionmentioning
confidence: 74%
“…We believe the future work outlined above will provide a path for continued improvements that ultimately allow for the direct coupling of MS with cryo-EM. Finally, we note that while this manuscript was under peer review, a preprint describing a similar cryogenic ion landing apparatus has been released by Esser et al Collectively, these joint works provide strong evidence for the potential impact of this exciting new field.…”
Section: Discussionmentioning
confidence: 74%
“…Native MS is also being leveraged to improve other structural biology techniques, such as soft-landing of mass-selected protein complexes for further structural characterization (e.g., cryo-electron microscopy). [407][408][409][682][683][684][685][686] Hydrogen deuterium exchange and protein footprinting have also seen substantive gains due to steady improvements in instrumentation. 168,[312][313][314]687,688 At the peptide level, methods for crosslinking MS (XL-MS) have enabled large-scale structural proteomics studies, owing in part to the advanced instrumentation discussed herein.…”
Section: Top-down Proteomicsmentioning
confidence: 99%
“…Most recently, a preprint has been published, that reported the combination of native MS with soft landing techniques. Here intact proteins were landed on cryoEM targets after ionization and mass spectrometry separation [82]. The resulting cryoEM data showed that the protein remained largely its original fold during native MS.…”
Section: Tools To Investigate Protein-metabolome Interactionsmentioning
confidence: 99%